PENINGKATAN KOMPETENSI SISWA DALAM IMPLEMENTASI INTERNET of THINGS DENGAN INTERFACE CLOUD - Abdul Basit; Very Kurnia Bakti; Ida Afriliana (Universitas Muhammadiyah Mataram, 2024)
Abstrak: Teknologi saat ini mengarah kepada revolusi industri 4.0 dimana segala lini kehidupan berbasis digital. Dengan teknologi Internet of Things (IoT) merupakan teknologi yang memungkinkan untuk mengontrol, berkomunikasi, berkolaborasi dengan berbagai perangkat keras. IoT bekerja dengan menghubungkan antar perangkat dengan jaringan internet, sehingga perangkat tersebut dapat berkomunikasi satu sama lain. Pengabdian Masyarakat ini bertujuan memberikan pengenalan tools dan komponen untuk membuat projek berbasis IoT. Sebelumnya pengenalan IoT ini sudah beberapa kali diperkenalkan, di beberapa SMK /SMA di sekitar Tegal. Dengan Demikian pengabdian Kepada Masyarakat ini perlu dilakukan untuk peningkatan hardskill. Metode pengabdian masyarakat ini adalah workshop dengan pemberian materi praktikum secara langsung, diikuti oleh 31 siswa SMA/SMK di Kota Tegal dan sekitarnya, ada 11 SMA/SMK yang mengirimkan perwakilannya, materi yang diberikan adalah Introduction (Pengenalan IoT), Instalasi Tools dan aplikasi, Implementasi Control Led Local Server dengan komponennya, Monitoring suhu dan kelembaban Berbasis Cloud. . Pemahaman para peserta cukup baik, terlihat dari hasil posttest, 90%, serta project yang dapat berjalan dengan baik.Abstract: Technology is currently leading to the industrial revolution 4.0 where all lines of life are digital-based. With technology, Internet of Things (IoT) is a technology that makes it possible to control, communicate, collaborate with various hardware devices. The IoT works by connecting between devices with the internet network, so that these devices can communicate with each other. The goals for this Community service is give the introduction tools of IoT anda components to build project based IoT. The introduction of the Internet of things has been introduced before, in several vocational or high schools around Tegal. Thus, this community service needs to be carried out because it is continuous with the introduction of the internet of things in the environment of high school students in the previous Tegal area, it is also necessary to introduce the components and implementation of devices used in this technology. This community service was attended by 31 high school / vocational high school students in Tegal City and surrounding areas, a total of 11 high schools/vocational high schools sent their representatives to participate in this activity, the material provided was Introduction (Introduction to IoT), Installation of Tools and applications, Implementation of Control Led Local Server with its components, Monitoring Cloud-based temperature and humidity. Thus increasing student competence is achieved in terms of knowledge in the field of internet of things. In terms of understanding, the participants have been able to absorb the material well, seen from the results of the training of the posttest 90% is good.